MORPHOLOGICAL CHANGES IN THE ADRENAL GLANDS OF RATS THREE HOURS AFTER EXPOSURE TO THE VENOM OF LEIURUS MACROCTENUS SCORPION - Kobzina-Didukh, D.S.; Fomina, L.V.; Tiron, O.I.; Kostiuchenko-Faifor, O.S.; Shapoval, О.М.; Damzin, O.S.; Kovalchuk, O.V. (World of Medicine and Biology, 2025)
Morphological examination of the adrenal glands of rats three hours after administration of Leiurus macroctenus scorpion venom revealed a marked progression of pathological alterations compared with earlier experimental time points. In the zona glomerulosa of the cortex, nuclear deformation, loss of the orderly arrangement of cellular clusters, and the appearance of intracellular edema were observed. The cytoplasm of endocrine cells lost its homogeneity, became granular, and exhibited perinuclear clear zones indicative of endoplasmic reticulum destabilization. In the zona fasciculata, a combination of physiological and pathological cellular hypertrophy was detected, accompanied by increasing intra- and extracellular edema. The nuclei of some cells were in stages of karyopyknosis and karyorrhexis, indicating the development of necrobiotic processes. In the zona reticularis, moderate hypertrophy, cytoplasmic basophilia, focal areas of edema, and infiltration by immunocytes were recorded. In the medullary substance, early manifestations of destruction were noted, including swelling of chromaffin cells, loss of distinct cellular boundaries, and nuclear deformation. The vessels of both the cortex and medulla exhibited signs of congestion, with aggregates of erythrocytes in their lumina. The capsule of the gland was characterized by moderate loosening of collagen fibers and morphological alterations in fibroblasts.
Keywords: anatomy; histology; adrenal glands; laboratory rats; venom of the scorpion Leiurus macroctenus